Enabling and disenabling boundary conditions of export marketing assistance: an interdisciplinary framework - Faroque Anisur; Torkkeli Lasse; Mahmud Hasan; Kuivalainen Olli (Inderscience, 2022)
Government-sponsored export marketing assistance programmes exert positive effects on the export performance of firms. However, the literature ignores the central concepts of international business (i.e., psychic distance and network), international marketing (i.e., export market orientation) and international entrepreneurship (i.e., international entrepreneurial orientation and prior international experience) when describing the use and effectiveness of export marketing assistance and its enabling and disenabling
boundary conditions. This study develops an interdisciplinary framework for export marketing assistance for early internationalising small- and medium sized enterprises by relating these pretermitted concepts. We suggest entrepreneurs’ prior international experience determines their use of export marketing assistance, while psychic distance moderates this relationship favourably and network unfavourably. Export market orientation (EMO) strengthens the export marketing assistance‒export performance relationship, while international entrepreneurial orientation (IEO) weakens the relationship. Policymakers and managers can use this model in ascertaining the optimal use of export marketing assistance.